Groundwater Quality Assessment for Drinking Purposes Using Multivariate Analysis and Surfer in Seremban, Negeri Sembilan - Yaacub, Umira; Kasmin, Hartini (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
Groundwater deterioration usually related to pollution that caused by human activities and natural sources that occurred underground. Water quality is important in order to maintain individual health. The objectives of this study were to determine the factor impacting groundwater quality for drinking purpose using multivariate statistical analysis and to generate groundwater contour map and flow direction using Surfer software. Multivariate analysis was used to analyze and identifying the element or factor that impacting the water quality in Seremban, Negeri Sembilan. Total ten parameters of five wells were analyzed. The results of descriptive analysis explained that based on the quality of physical and chemical parameters, water from these five wells are suitable to be used as drinking water. The qualities are all below the limit recommended by Ministry of Health (MOH) and World Health Organization (WHO), except for electrical conductivity (EC) and bicarbonate (HCO3) parameters. Hierarchical analysis result was then classified the groundwater into three cluster. Cluster 1 has less salinity type of water and Cluster 2 it might cause by the replenishment of freshwater. For Cluster 3, value of EC has the highest compared to others at 508.00 µS/cm. In principal cluster (PC) analysis or factor analysis, result shows that PC2 (Principal for Cluster 2) has the total variance of 11.91%. This PC2 result indicated that source of pollution in the groundwater sample is might due to anthropogenic activities such as agriculture, urbanization, and natural sources (mineral dissolution) based on previous studies. The generation of water table map using Surfer software shows that the groundwater is flowing from East to West direction of Seremban map.